Semi-synthetic minimal cells: Biochemical, physical, and technological aspects - Stano, Pasquale; de Souza, Tereza Pereira [UNESP]; Kuruma, Yutetsu; Carrara, Paolo; Luisi, Pier Luigi (Elsevier, 2013)
The construction of synthetic cells is one of the major goals of bioengineering. The most successful approach consists in the encapsulation of biochemical materials (DNA, RNA, enzymes, etc.) inside lipid vesicles (liposomes), mimicking a cell structure. In this contribution, that also aims at introducing the reader to 'chemical synthetic biology,' we describe the current state of the art of 'semi-synthetic minimal cells' (SSMCs), namely, cell-like structures containing the minimal number of biological compounds that are required to reconstruct a function of interest. We will first describe how the concept of the minimal cell was originated and its relation with the theory of autopoiesis, then we review the most advanced results focused on genetic/metabolic networks inside liposomes. Next, we emphasize that relevance of physical aspects (too often neglected) that impact on the solute entrapment process, and finally we discuss new technological trends in SSMC research that will probably allow their future use in biotechnology. © 2013 Copyright © 2013 Elsevier Inc. All rights reserved.
Keywords: Autopoiesis; Cell-free; Liposomes; Minimal cell; Origin of life; Protein synthesis; Self-organization; Self-reproduction; Synthetic biology